Critical reflection and the foreign language classroom - Osborn, Terry A., 1966- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Twenty years ago, this book introduced pre-service and in-service foreign language teachers to the basic concepts of critical educational study as applied to foreign language education in the United States. Since its initial publication, teachers now commonly known as world language educators are better prepared to understand issues of power in relation to, for example, language variety, language status, and language education. Indeed, much recent attention has been focused on critical approaches to language education including teaching for social justice. The author addresses issues such as the supposed "failure" of foreign language education, the educational filter role played by language classes, the concept of foreignness as seen in national standards, language curricula and textbooks, and the implications of these issues in terms of power relationships and cultural mediation both in and out of the classroom. The reader is encouraged to analyze the forms of cultural struggle which can be found within the world language classrooms of the United States including the likely impact those struggles have on members of the dominant and subordinate cultures. Two decades later critical reflection continues to require these skills"-- Provided by publisher.
Keywords: Language and languages -- Study and teaching -- United States.; Education -- Language Experience Approach.; Language learning: specific skills.; Teaching skills and techniques.; elektronické knihy; electronic books